Role of microRNA in regulation of synaptic plasticity during post-traumatic stress disorder. (2023) - Kumar, Prabhat; Gautam, Akash
Graphical abstract: Abstract: Post-traumatic stress disorder (PTSD) is an incapacitating mental condition that develops after exposure to a disconcerting event. Failure to forget traumatic memories can lead to the development of fear memory associated with PTSD. Recent research exploring the molecular mechanism of memory dysfunction during PTSD was based on histone modification and DNA methylation, ignoring the role of non-coding sequences such as micro RNA (miRNA). Therefore, we review how miRNA regulates synaptic plasticity genes during PTSD-associated fear memory consolidation and extinction. We hypothesize that the miRNA will increase the expression of different synaptic plasticity genes in different brain subregions during PTSD. Since available treatment options are not sufficient, identifying new therapies is essential. More studies can define a therapeutic window for such interventions, helping to spread alternative supportive therapies for the treatment of PTSD. Moreover, our discussion might shed new light on the significance of miRNA (miRNA- 142) in regulating synaptic plasticity genes.